ISLAMIC POLITICAL THOUGHT AS IBADAH: Reinterpreting Hassan Hanafi’s Progressive Vision - Huda, Khoirul; Yudha, Dian Pratama; Ibbna, Mulazi (UIN Sumatera Utara, 2025)
Research on Hassan Hanafi's political thought focuses on three main aspects. First, the concept of